Prevalence of dyslipidemia in normoglycemic subjects with newly diagnosed high blood pressure in Abuja, Nigeria. (2009)
The H3Africa Consortium (2014). Enabling the Genomic Revolution In Africa. American Association for the Advancement of Science: . 1346-1348pp. ISBN: 1612309842 (United States of America ) (Contribution : 20%) h. Background: High blood pressure and dyslipidemia additively increases the risk of cardiovascular disease. There is a high prevalence of high blood pressure in Nigeria, but there are little data regarding the prevalence of dyslipidemia in subjects with high blood pressure. OBJECTIVE: In this observational prospective study, we examined the prevalence of dyslipidemia in newly diagnosed normoglycemic subjects with high blood pressure. Methods: A total of 171 subjects presenting with high blood pressure for the first time in the cardiology and nephrology clinics at the University of Abuja Teaching Hospital were studied. Height, weight, and blood pressure were measured. Total cholesterol, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were determined in fasting plasma. The total cholesterol/HDL-C and non–HDL-C values were calculated. These measures were then classified according to the 2001 report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults. RESULTS: Of the 171 subjects studied, 84 (49%) were male and 87 (51%) were female. Low HDL-C was present in 71 (45.8%), elevated LDL-C in 29 (17%), elevated total cholesterol in 19 (11.1%), and elevated triglyceride in 13 (7.6%), whereas eight (4.7%) of the study population had combined elevated total cholesterol and triglyceride. Female subjects had higher total cholesterol and lower HDL-C than male subjects, but these differences were not statistically significant. Obese subjects, compared to the nonobese, had significantly higher LDL-C and total cholesterol/HDL-C ratios in males and significantly higher triglyceride levels in females. Conclusions: Given the prevalence of dyslipidemia seen in this study, we suggest that fasting lipid measurements should be performed in all Nigerians with high blood pressure. These data suggest the need for health education and lifestyle modifications in hypertensive Nigerians to reduce both types of risk factors.